2012
DOI: 10.3144/expresspolymlett.2012.83
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of polybenzoxazine modified with isomeric biphenyltetracarboxylic dianhydrides

Abstract: Abstract.A series of polymeric alloying films were prepared from bisphenol A/aniline-based bifunctional benzoxazine resin (BA-a) with three isomeric biphenyltetracarboxylic dianhydrides, i.e., 2,3!,3,4!-biphenyltetra carboxylic dianhydride (a-BPDA), 2,2!,3,3!-biphenyltetracarboxylic dianhydride (i-BPDA), and 3,3!,4,4!-biphenyltetracarboxylic dianhydride (s-BPDA) through fully thermal curing. Chemical structure, thermomechanical property and thermal stability of bisphenol A/aniline type polybenzoxazine (PBA-a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Therefore, the flmmability characteristic of the 65 wt% carbon fiber‐reinforced BA‐a/PMDA copolymer composites can be retarded with PMDA content increased with observation of reduced burning time in Table , suggesting that an addition of the PMDA into the poly(BA‐a) matrix of the carbon fiber composites can help improve the fire resistance of the composites due to carbonaceous char barrier formation that results in blocking of available oxygen caused by the generation of combustion barriers and delay of flame propagation by adiabatic effect. This result is in good agreement with our previous work reported that the char yield value of polybenzoxazine modified with dianhydrides copolymers were much higher than that of the neat poly(BA‐a). In principle, the higher char residue of the copolymer can provide a sample with enhanced flammability because char formation can inhibit volatile products from diffusing to the flame and shield the polymer surface from heat and air .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the flmmability characteristic of the 65 wt% carbon fiber‐reinforced BA‐a/PMDA copolymer composites can be retarded with PMDA content increased with observation of reduced burning time in Table , suggesting that an addition of the PMDA into the poly(BA‐a) matrix of the carbon fiber composites can help improve the fire resistance of the composites due to carbonaceous char barrier formation that results in blocking of available oxygen caused by the generation of combustion barriers and delay of flame propagation by adiabatic effect. This result is in good agreement with our previous work reported that the char yield value of polybenzoxazine modified with dianhydrides copolymers were much higher than that of the neat poly(BA‐a). In principle, the higher char residue of the copolymer can provide a sample with enhanced flammability because char formation can inhibit volatile products from diffusing to the flame and shield the polymer surface from heat and air .…”
Section: Resultssupporting
confidence: 93%
“…From the results, the T g value substantially enhanced with the incorporation of PMDA into the composites. This phenomenon is due to the presence of greater aromatic content and the increased crosslink density via ester linkage between hydroxyl group of poly(BA‐a) and anhydride group of PMDA in the copolymer structures . Furthermore, loss tangent (tan δ) of 65 wt% carbon fiber‐reinforced poly(BA‐a) and 65 wt% carbon fiber‐reinforced PMDA‐modified poly(BA‐a) composites at various mol ratios of PMDA are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, all alloy films of PBAa:PA, PBA-a:NA, PBA-a:PMDA and PBA-a:NTDA demonstrated significantly toughness in comparison with the neat PBA-a. The flexibility enhancement of all alloy samples is attributed to additional ester linkages, structurally flexible functional group, formed in the PBA-a network as a result quoted in previous publications [21][22][23][24].…”
Section: Resultsmentioning
confidence: 76%
“…Moreover, the free carboxylic acid vibration band occurred after thermal curing of the alloys can also be observed as a band at 1669-1651 cm −1 attributed to C=O stretching band [29]. The reaction models of those monoanhydrides and dianhydrides modified PBA-a alloys are proposed and shown in Scheme 1 as similar to our previous works [21][22][23]. The reaction was also like to the ester formation between a diglycidyl ether of bisphenol A based epoxide resin (DGEBA) and dodecyl succinic anhydride (DDSA) as reported by Ghaemy and Riahy [30].…”
Section: Resultsmentioning
confidence: 82%
“…The obtained copolybenzoxazine at a weight ratio of 1/1 showed a relatively low dielectric constant of 2.36, compared with the value of about 3.56 for the polybenzoxazine without fluorine atoms in its structure. The second approach to enhancing the properties of polybenzoxazine is copolymer formations of the polybenzoxazine with other resins or polymers such as polyimide, polyurethanes, epoxy, and anhydride . Recently, Jubsilp et al .…”
Section: Introductionmentioning
confidence: 99%